How do you solve by substitution 4x + 6y = 62 and 10x - 2y = 2?

1 Answer
Jun 5, 2015

10x-2y=2
10x=2+2y ( we add 2y on each side )
10x-2=2y ( we substract 2 on each side )
5x-1=y ( we divide by 2 on each side )

Now that we have y, we can use substitution in the first equation :

4x+6*(5x-1)=62
4x+30x-6=62
34x-6=62
34x=62+6 ( we add 6 on each side )
34x=68
x=68/34=2 ( we divide by 34 on each side )

Now that we have x, we can find y :

We know that y=5x-1, as we calculated it before :

y=5*2-1=10-1=9